Crisis leadership : how to lead in times of crisis, threat and uncertainty - Johnson, Tim (Timothy Byron), 1977- (London ; New York, NY : Bloomsbury Business, 2018)
Anyone in a leadership position is only too aware that we live in uncertain times: disaster can strike any business, at any time, and usually without warning. Public institutions, too, face a range of threats - from global recession, resurgent terrorism and a stream of appalling natural disasters. For leaders in such organisations, these crisis situations can present both opportunities and threats. How they lead through such challenging times will propel their careers to new heights - or destroy them completely. Crisis Leadership examines the challenges faced by leaders at each stage of the crisis 'lifecycle', from the instant they learn of the crisis, through to moments of critical decision-making and the final tumultuous days. Tim Johnson offers a unique insight into the lessons learned by people in the most challenging of situations. Blended with operational guidance from the author's extensive experience in crisis management, Crisis Leadership provides an overview of the crisis 'lifecycle', to ensure that readers will come away from this book with a deeper appreciation of the critical nature of each key stage and the leadership challenges they bring - from the first signs of an emerging crisis to dealing with the long-term consequences they can create. -- Provided by publisher.
Introduction -- What is a crisis? And, what is effective crisis leadership? -- Giving ourselves a fighting chance of succeeding -- Commencing crisis leadership -- The challenges of making decisions and setting (early) strategy -- Crisis team leadership -- Crisis leadership in public -- Crisis leadership in private -- When crisis leadership ends -- Preparing crisis leaders.
Includes bibliographical references (pages 239-246) and index.
Keywords: Crisis management; Leadership